Pemanfaatan Pupuk Kandang Kambing dan Pupuk Urea terhadap Pertumbuhan dan Produksi Pakcoy (Brassica rapa chineensis L.) - Desta Sahedi Surbakti; Ahmad Sofian; Erlita Chaniago (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2026)
This study aims to determine the effect of goat manure and urea fertilizer and the interaction of the two fertilizers on the growth and production of pakcoy plants (Brassica rapa chineensi L). The study was conducted on Jl. Tuntungan II, Pancur Batu District, North Sumatra Province, from April to May 2024. This study used a Factorial Randomized Block Design with 2 factors studied and 3 replications where the first factor was goat manure (K) which consisted of 3 levels, namely K0 = (Control), K1 = (2 kg plot-1), K2 = (4 kg plot-1). The second factor is Urea Fertilizer (U) which consists of 4 levels, namely U0 = (Control), U1 = (7.5 g plot-1), U2 = (15 g plot-1), U3 = (22.5 plot-1). The parameters observed were plant height (cm), number of leaves (strands), leaf area (cm2), weight sample-1 (g), and weight plot-1 (g). The results showed that the provision of goat manure had a significant effect on plant height, number of leaves, and leaf area, but had no significant effect on weight per sample and weight per plot. The provision of urea fertilizer had no significant effect on all observed parameters. The interaction of goat manure and urea fertilizer had no significant effect on plant height, number of leaves, leaf area, weight per sample, and weight per plot.